Best Practice Pengembangan dan Penerapan Teknologi Tepat Guna - Megawati, Megawati; Adianto, Adianto (Jurnal Ilmu Administrasi Negara (JUAN), 2021)
Kundur village developed appropriate technology to assist the community in doing their daily work as farmers. The peat land owned by Kundur is very fertile and provides prosperity, but the water produced by peat soil is not good for consumption. Meanwhile, during the dry season, the rainwater supply runs out, the community uses peat well water for consumption. This prompted the village government to take the initiative to submit a proposal to the Ministry of Village for PDDT with a request for an appropriate tool to process peat water into drinking water, the idea was approved and assistance channeled through the implementation team of the Pilot Program for the Local Economic Development Innovation Association Pilot Program and implemented in Kundur Village. This study aims to see how the process of developing and implementing appropriate water management in Kundur village and the inhibiting factors that affect it. Using qualitative research methods with a descriptive case study approach. The theoretical concept used is theory (Prasojo, Eko, 2007), there are several criteria for assessing best practices that are adjusted to the PDDT Ministerial Regulation No. 23 of 2017 concerning the development and application of appropriate technology in natural resource management. The results of the study found that the application of appropriate technology for managing peat water into clean water in Kundur was successfully implemented and had a good impact on the lives of the community and the Kundur village government. However, this application is not yet correct because inhibiting factors are still found in the development and application of technology for water management in Kundur, namely marketing strategies, incomplete legal legality, and minimal budget.